In vitro bioactivities of Codonopsis javanica root extract from Kon Tum province, Vietnam - Pham Thi, Hai Ha; Tran, Kien Cuong; Nguyen, Thi Thu Nha; Hoang Nguyen, Lan Phan; Nguyen Huu, Thuan Anh; Bach, Long Giang; Than, Thi Minh Phuong; Chu, Dinh Lieu; Le, Van Thanh; Nguyen, Thanh Luan (Hue University Journal of Science: Natural Science, 2022)
Dangshen Codonopsis javanica exhibits invaluable medicinal properties in herbal remedies; however, there has currently not been much specific analysis of the phytochemicals and bioactivities of this plant. The root ethanol extract of C. javanica contains substances such as saponins, phenolic acids, terpenoids, and alkaloids. It displays an antibacterial effect against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus cereus with the IC50 values of 150, 100, 150, and 90 μg/mL, respectively. The antioxidant capacity of the root extract was also observed with an IC50 value of 46.8 ± 6.8 μg/mL. Furthermore, the extract exhibits activity on human cancer cell lines HepG2 (IC50 = 83.6 ± 2.7 μg/mL) and MCF-7 (IC50 = 95.3 ± 2.3 μg/mL). Hence, this study provides the basic data for further research on the bioactivities of natural compounds of Dangshen C. javanica for the first time.